2016
DOI: 10.1021/acs.jnatprod.5b00798
|View full text |Cite
|
Sign up to set email alerts
|

pks63787, a Polyketide Synthase Gene Responsible for the Biosynthesis of Benzenoids in the Medicinal Mushroom Antrodia cinnamomea

Po-Wei Yu,
Ya-Chih Chang,
Ruey-Fen Liou
et al.

Abstract: Antrodia cinnamomea, a unique resupinate basidiomycete endemic to Taiwan, has potent medicinal activities. The reddish basidiocarps and mycelia generally exhibit abundant metabolites and higher biological activity. To investigate the pigments of A. cinnamomea, polyketide synthase (PKS) genes were characterized based on its partially deciphered genome and the construction of a fosmid library. Furthermore, a gene disruption platform was established via protoplast transformation and homologous recombination. Of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
(84 reference statements)
1
17
1
1
Order By: Relevance
“…Under the conditions obtained, it showed that the mycelial cell wall was almost completely digested, and no further filtration step was required to remove the cell wall debris ( Figure S1). The number of protoplasts obtained was 2.1 Â 10 8 cells mL À1 which was much higher than earlier studies when compared with the literature on the preparation of protoplasts of A. cinnamomea [18].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Under the conditions obtained, it showed that the mycelial cell wall was almost completely digested, and no further filtration step was required to remove the cell wall debris ( Figure S1). The number of protoplasts obtained was 2.1 Â 10 8 cells mL À1 which was much higher than earlier studies when compared with the literature on the preparation of protoplasts of A. cinnamomea [18].…”
Section: Discussioncontrasting
confidence: 51%
“…As shown in Figure 9, it had the highest regeneration rate of 71.3% at 80 mM citrate buffer in this experiment. The protoplast regeneration rate is dramatically increased from earlier report of 6.8% [18] to 71.3%. Based on the above optimal condition for protoplast regeneration of A. cinnamomea, it is easier for observation of subsequent results of protoplast regeneration, such as shown in Figure 10.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, the TE domain of A. nidulans OrsA in group I catalyzes an intermolecular transesterification during biosynthesis of lecanoric acid ( Gressler et al, 2015 ). Besides cross-coupling activity, the TE domains of NR-PKSs in group VIII often perform hydrolysis activity to produce orsellinic acid ( Lackner et al, 2013 ; Yu et al, 2016 ). The complex phylogeny revealed that the evolution of TE domains was accompanied by functional divergence from hydrolysis to cross-coupling to macrolactone closure.…”
Section: Resultsmentioning
confidence: 99%
“…Very few PKSs from mushrooms have been investigated. All of them were identified as orsellinic acid synthases, [13,20] that is, none of them represents a HR-PKS and none of the previous studies investigated the interrelation between an enzyme, its product, and the function for the producing organism.Therefore, our results highlight that a single PKS gene is sufficient to induce chemical defense (Figure 4). Genes for highly similar synthases were identified in basidiomycetes of various evolutionary clades.…”
mentioning
confidence: 99%